Consistent Individual Differences and Plasticity in Migration Behaviour of Three North American Ungulates - Michel P. Laforge; Eric Vander Wal; Quinn M. R. Webber; Chris Geremia; Matthew J. Kauffman; Douglas E. McWhirter; Arthur Middleton; Tony W. Mong; Kevin L. Monteith; Anna C. Ortega; Hall Sawyer; Jerod A. Merkle (Ecology Letters, 2025)
Migratory herbivores often time spring migration to coincide with the green‐up of plants. When the timing of green‐up changes across years, herbivores can respond directly and be plastic to changing conditions or populations may adapt via inherent differences among individuals that may allow for an evolutionary response. We quantified plasticity and individual variation in the timing of spring migration and selection for high‐quality forage as a function of the timing of spring green‐up using behavioural reaction norms for three North American ungulate species. The timing of arrival to summer range (but not departure from winter range) was plastic to the timing of green‐up, and both arrival and departure timing were repeatable. Our results suggest that herbivores synchronise migration with the timing of green‐up by adjusting the pace of migration and may be buffered against change via individual differences. Quantifying plasticity and differences in responses represents a crucial step to elucidating the fate of species in a changing world.